The Relationship Between Critical Thinking and Clinical Decision-Making in Emergency Nurses of Hospitals Affiliated to Zanjan University of Medical Sciences in 2020 - Hadi Khanmoradi; Ali Aghajanloo; Mohammadreza Dinmohammadi; Farhad Ramazani-Badr (Zanjan University of Medical Sciences and Health Services, 2021)
Background: Critical thinking is a purposeful and self-directed judgment that is achieved through interpretation, analysis, evaluation, and inference. It makes nurses able to reason correctly about patient problems and issues and make the right decisions. Objectives: The aim of this study was to investigate the status of critical thinking and clinical decision-making and determine their relationship with emergency department nurses. Methods: This descriptive correlational study was performed among 320 nurses in the emergency department of hospitals affiliated to Zanjan University of Medical Sciences selected by available census method. The research instruments included the California Critical Thinking Skills Test (CCTST) and the 2014 Clinical Decision Making Scale (CDMS) by Lauri et al. Data analysis was performed using SPSS 19 software and descriptive and analytical statistics. Results: The mean scores of clinical decision-making and critical thinking were 81.5±1.35 and 10.05±3.13, respectively. There was a weak and significant positive correlation between clinical decision-making and critical thinking (r=0.133, P=0.001). Clinical decision-making was significantly associated with age, gender, and work experience, and critical thinking was significantly associated with age, education, and work experience (P<0.05). Conclusion: Due to the poor critical thinking skill and the weak relationship between critical thinking and clinical decision-making observed, it is recommended to hold training and empowerment courses to strengthen critical thinking skills in nurses. On the other hand, strengthening critical thinking can improve nurses' clinical decision-making skills.